2-Deoxyglucose conjugated platinum (II) complexes for targeted therapy: design, synthesis, and antitumor activity. Issue 11 (1st November 2016) - Mi, Qian; Ma, Yuru; Gao, Xiangqian; Liu, Ran; Liu, Pengxing; Mi, Yi; Fu, Xuegang; Gao, Qingzhi
Abstract : Malignant neoplasms exhibit an elevated rate of glycolysis over normal cells. To target the Warburg effect, we designed a new series of 2-deoxyglucose (2-DG) conjugated platinum (II) complexes for glucose transporter 1 (GLUT1)-mediated anticancer drug delivery. The potential GLUT1 transportability of the complexes was investigated through a comparative molecular docking analysis utilizing the latest GLUT1 protein crystal structure. The key binding site for 2-DG as GLUT1's substrate was identified with molecular dynamics simulation, and the docking study demonstrated that the 2-DG conjugated platinum (II) complexes can be recognized by the same binding site as potential GLUT1 substrate. The conjugates were synthesized and evaluated for in vitro cytotoxicity study with seven human cancer cell lines. The results of this study revealed that 2-DG conjugated platinum (II) complexes are GLUT1 transportable substrates and exhibit improved cytotoxicities in cancer cell lines that over express GLUT1 when compared to the clinical drug, Oxaliplatin . The correlation between GLUT1 expression and antitumor effects are also confirmed. The study provides fundamental information supporting the potential of the 2-DG conjugated platinum (II) complexes as lead compounds for further pharmaceutical R&D.